PENYULUHAN TENTANG DIABETES MELLITUS DI WILAYAH KERJA UPT BLUD PUSKESMAS SALO - Rizki Rahmawati Lestari; Zurrahmi (Universitas Pahlawan Tuanku Tambusai, 2022)
Diabetes is one of the most common and serious chronic diseases in Indonesia today. Half of the cases of Diabetes Mellitus (DM) are undiagnosed because in general diabetes is not accompanied by symptoms until complications occur. The prevalence of diabetes is increasing due to changes in lifestyle, an increase in the number of calories eaten, a lack of physical activity and an increasing number of the elderly human population. With the increasingly advanced socio-economic conditions of the Indonesian people as well as better and more equitable health services, it is estimated that the incidence of diabetes mellitus (DM) will increase. From the survey results, it was found that the number of DM patients at the Adult Poly Health Center in Salo was the second of the 10 most diseases. Based on data obtained in 2020 the number of diabetes patients increased to 1256 patients. While data on knowledge of nutrition and eating patterns obtained 7 out of 10 patients with diabetes mellitus due to lack of knowledge of nutrition and poor eating patterns. Type II DM in Indonesia is a non-communicable disease or 2.1% of all deaths. Given the increasing incidence of diabetes mellitus and the dangers of complications, it is necessary to conduct health education and examinations about hypertension, including blood glucose levels (KGD) examinations so that the elderly in the UPT BLUD Work Area of ​​the Salo Health Center can monitor their health conditions and control KGD younger. Keywords: Diabetes Mellitus, Counseling